Using endogenous ligands for direct superparamagnetic nanoparticle cluster-based body fluid exosome separation. Issue 5 (12th January 2017) - Qi, Hongzhao; Jia, Huanhuan; Sang, Jimeng; Ren, Yu; Zhao, Jin; Hou, Xin; Yuan, Xubo
Abstract : Using endogenous ligands to directly separate exosomes from body fluids facilitates the in vivo clinical translation of exosomes. Abstract : The separation and purification of exosomes is essential for the application of exosomes. Previously we have developed a new strategy based on superparamagnetic nanoparticle clusters for the separation of exosomes. Here, to optimize this method for the direct separation of body fluid exosomes using endogenous ligands, we unveiled the influence of free ligands on the formation of clusters and the efficiency of exosome separation. Transferrin was chosen as a model endogenous ligand and the concentration of free serum transferrins was adjusted by different times of serum dialysis. To directly separate most of the exosomes from 1 mL untreated serum, at least 360 μg of labelled ligands needed to be used. However, the required amount of labelled ligands reduced to 10 μg when serum was pre-dialyzed for 24 hours. The results demonstrate that the free ligands can compete with ligands labelled on superparamagnetic nanoparticles to affect the formation of clusters. And to separate exosomes from body fluids sufficiently and directly, the amount of labelled ligands must reach a minimum value ( i.e., equivalent to the amount of free ligands). In addition, eliminating free ligands by the mild pre-treatment of body fluids facilitates the separation and purification of body fluid exosomes. This study can improve the universality of current immunoaffinity magnetic particle-based methods for exosome separation and facilitate the in vivo clinical translation of exosomes.